Enzyme‐Mediated In Situ Buildup and Site‐Specific Addressing of Polymeric Coatings. Issue 1 (26th November 2018) - Appel, Daniel; Wedegärtner, David; Lüther, Marco; Strube, Oliver I.
Abstract: Formation of site‐specific deposition of polymeric particles and films with controllable parameters via enzyme‐mediated addressing is investigated. The polymers are synthesized in situ by combining the addressing process with enzyme‐mediated radical polymerization, using the enzyme horseradish peroxidase. As a model system, the technically important poly(methyl methacrylate) is formed and addressed on both glass‐ and polyethylene supports. The key to the controllability is the influence of different reaction parameters on particle formation, namely, the concentration of H2 O2 and the pH show the most significant impact. With higher concentrations of H2 O2, size and amount of gained particles increases, due to H2 O2 being a limiting factor to the reaction. Moreover, since acetyl acetone forms the end‐group of the polymer chains, the pH directly influences the particle stability in addition to affecting the enzyme activity. This effect can be utilized to gain either films or particle assemblies at will. Deposition occurs highly site‐specific, exclusively on enzyme‐functionalized areas, enabling patterned coating structures within a safe, energy efficient, and easy‐to‐apply process. Abstract : A novel approach for the formation of site‐specific coatings from synthetic polymers via a twofold utilization of enzymatic catalysis is presented. This extension of enzyme‐mediated addressing strongly increases the variety of this technique. It is now possible to produce patterned coatings from mass polymers with defined characteristics in a safe, energy‐efficient, and easy‐to‐apply manner.